Soil aggregation and associated microbial communities modify the impact of agricultural management on carbon content. (22nd June 2017) - Trivedi, Pankaj; Delgado‐Baquerizo, Manuel; Jeffries, Thomas C.; Trivedi, Chanda; Anderson, Ian C.; Lai, Kaitao; McNee, Matthew; Flower, Kenneth; Pal Singh, Bhupinder; Minkey, David; Singh, Brajesh K.
Summary: Soil carbon (C) stabilisation is known to depend in part on its distribution in structural aggregates, and upon soil microbial activity within the aggregates. However, the mechanisms and relative contributions of different microbial groups to C turnover in different aggregates under various management practices remain unclear. The aim of this study was to determine the role of soil aggregation and their associated microbial communities in driving the responses of soil organic matter (SOM) to multiple management practices. Our results demonstrate that higher amounts of C inputs coupled with greater soil aggregation in residue retention management practices has positive effects on soil C content. Our results provide evidence that different aggregate size classes support distinct microbial habitats which supports the colonisation of different microbial communities. Most importantly our results indicate that the effects of management practices on soil C is modulated by soil aggregate sizes and their associated microbial community and are more pronounced in macro‐aggregate compared with micro‐aggregate sizes. Based on our findings we recommend that differential response of management practices and microbial control on the C turnover in macro‐aggregates and micro‐aggregate should be explicitly considered when accounting for management impacts on soil C turnover.